Strain rate effect on tensile behavior of AA6061-T6 friction stir welds. (November 2021) - Kumar, Indrajeet; Bhattacharya, Anirban
Abstract: The present study aims to assess the mechanical, strain hardening and fracture behavior of the AA6061-T6 similar FSW joints under uniaxial tensile test performed at different strain rates ranging from quasi-static to moderately high ( 10 - 5 to 10 - 1 /s). The joints showed strain rate dependent behavior and yield strength, ultimate tensile strength of the joints is observed to slightly increase with decrease in strain rate. Strain hardening behavior shows stage III and IV hardening only and higher hardening capacity of the joints is observed than the base metal. Grain elongation and strain accumulation is observed from the electron back scatter diffraction analysis of the joints after tensile testing at different strain rates. Ductile fracture with ductile tear ridges on the fracture surfaces along with large quantities of uniform and equiaxed dimples are observed on fracture surfaces of the joints.